2017
DOI: 10.1016/j.electacta.2016.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Initial stages of Pt(111) electrooxidation: dynamic and structural studies by surface X-ray diffraction

Abstract: In-situ surface X-ray diffraction is used to characterize the surface oxides on Pt(111) surface in 0.1 M HClO 4. Detailed analysis at two potentials confirms that the surface restructuring at the initial oxidation stages is consistent with a place exchange process between Pt and O atoms, and the exchanged Pt atoms are located above their original positions in the Pt(111) lattice. The (1,1,1.5) reflection is used to dynamically study the surface during cyclic voltammetry. The restructuring associated with the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
131
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(155 citation statements)
references
References 65 publications
22
131
0
Order By: Relevance
“…[27][28][29][30][31][32][33][34] As an extension of our previous work, 5 we consider a non-ideal solid solution of Pt and hydroxide/oxides whose composition can be determined by considering the following reactions, which are supported by experimental evidence from the extensive Pt oxidation literature. PtOH…”
Section: Modeling Of Pt Dissolutionmentioning
confidence: 99%
“…[27][28][29][30][31][32][33][34] As an extension of our previous work, 5 we consider a non-ideal solid solution of Pt and hydroxide/oxides whose composition can be determined by considering the following reactions, which are supported by experimental evidence from the extensive Pt oxidation literature. PtOH…”
Section: Modeling Of Pt Dissolutionmentioning
confidence: 99%
“…In-situ SXD revealed that site exchange of Pt and O occurs at 1.1 V(RHE) on Pt(111). 21 There have been no study on Pt oxides using in-situ vibrational spectroscopy on well-defined single crystal electrodes. In this section, we summarize our recent studies of Pt oxides on single crystal electrodes of Pt using IRAS and NPSERS.…”
Section: -64mentioning
confidence: 99%
“…75 However, the onset potential of PtO and PtO(H) formation in NPSERS is 1.15 V(RHE) where coverage of PtO reaches full coverage and place exchange occurs between Pt and O. 21 Strong electric field of plasmon may expel PtO from the neighborhood of Au nanoparticles at lower coverage of PtO. 74 Figure 13 shows the integrated band intensity of NPSERS plotted against the applied potentials.…”
Section: Iras Measurement Of Ptohmentioning
confidence: 99%
See 2 more Smart Citations